Perilous memories : the Asia-Pacific War(s) - Fujitani, Takashi; White, Geoffrey M. (Geoffrey Miles), 1949-; Yoneyama, Lisa, 1959- (e-Duke books scholarly collection., 2001)
A rethinking of the differing national memories of the Second World War in the Pacific in light of recent theories of nationalism, imperialism, and colonialism.